A Comparative Study of the Financial Performance of Rural Banks (BPR) in Bali Province Before and After the Emergence of Financial Technology (Fintech) - Desak Ayu Wedayani; Ida Bagus Anom Purbawangsa (International Forum of Researchers and Lecturers, 2025)
The emergence of fintech services requires banks to enhance their competitive advantage through technological innovation and digitalization, compelling Rural Banks (BPR) to adapt in order to remain relevant in an increasingly competitive environment. This study aims to analyze the differences in BPR financial performance before and after the introduction of fintech services, with a focus on capital adequacy, profitability, and liquidity for the period 2019–2023. The sample consists of 21 BPRs in Bali Province, selected using non-probability sampling with purposive sampling techniques based on specific criteria. Data were collected through non-participant observation. The data analysis techniques employed include normality testing and the Wilcoxon signed-rank test. The results reveal that both Capital Adequacy Ratio (CAR) and Return on Assets (ROA) of BPRs increased after the implementation of fintech services, whereas the Loan to Deposit Ratio (LDR) decreased. The theoretical implication of this study supports Schumpeter’s theory of innovation, which asserts that technological innovations such as fintech services drive qualitative changes in the economic system through the creation of new products, enhancement of service quality, development of operational methods, and the opening of new markets, thereby improving BPR financial performance. The practical implication of this study is to provide insights for BPRs in formulating strategies to improve financial performance, and for potential customers, BPR health indicators may serve as a reference in assessing the reputation of BPRs and building customer trust, which in turn influences their financial performance.